Reducing impact loading during running with the use of real-time visual feedback - Crowell, H. P.; Milner, C. E.; Hamill, J.; Davis, I. S. (Journal of Orthopaedic & Sports Physical Therapy, 2010)
STUDY DESI GN: Single-subject with repeated measures. OBJECTIVES : To determine if runners can use real-time visual feedback from an accelerometer to achieve immediate reductions in tibial acceleration and vertical-force loading rates. BACKGROUND: Stress fractures are a common injury among runners. Previous studies suggest that runners with higher than normal tibial acceleration and vertical-force loading rates are at increased risk for tibial stress fractures. If these runners can be trained to reduce the loading on their lower extremities, it may reduce their risk of stress fractures. METHODS: Five subjects participated in this study. All subjects ran on a treadmill, instrumented with force transducers, during a single 30-minute session that was divided into warm-up, feedback, no-feedback, and cool-down periods. During running, the subjects also wore an accelerometer taped to their distal right tibia. Peak positive acceleration of the tibia, vertical force impact peak, and average and instantaneous vertical-force loading rates were assessed at the end of the warm-up, feedback, and no-feedback periods. RES ULTS: Single-subject analysis revealed that 4 of the 5 subjects had significant reductions in their peak positive acceleration at the end of the no-feedback period compared to the warm-up. In addition, all of the subjects had significant decreases in impact peak and vertical ground reaction force loading rates at the end of the no-feedback period. CONCLUSION : In a single session of training with real-time visual feedback, it appears that most runners can reduce the types of lower extremity loading associated with stress fractures. This may lead to training programs that